Jet production at electron-positron colliders at next-to-next-to-next-to-leading order in QCD - Xuan Chen; Petr Jakubčík; Matteo Marcoli; Giovanni Stagnitto (Physics Letters B)
We present the first application of antenna subtraction at next-to-next-to-next-to-leading order (N3LO) in QCD by computing fully differential predictions for two-jet production at electron-positron colliders. We illustrate the structure of the infrared counterterms and provide results for the N3LO correction to the two-jet production rate and to the leading-jet energy. Our work constitutes the first direct calculation of jet production at electron-positron colliders at N3LO and represents the first step in tackling arbitrary processes with jets at this perturbative order.